L’applicazione delle tecnologie fotovoltaiche integrate sulle coperture degli edifici con software GIS - Bonesso, Stefano; Mutani, Guglielmina; Hubina, Tatsiana; Ramassotto, Adelaide (GEOmedia, 2013)
Per pianificare l'utilizzo di tecnologie che sfruttano energia rinnovabile su un territorio, in particolare quelle che riguarda il solare, si possono utilizzare i software GIS (Sistemi Informativi Geografici) che consentono di analizzare e rappresentare un dato geo-riferito. Potential of photovoltaic technologies on buildings' roofs using geographic information systems (GIS) - In order to plan the diffusion of renewable energy technologies, geographic information systems (GIS) can be useful. In this study photovoltaic technologies in urban environments were examined, considering the shadows of urban contest and of territory orography evaluated with GIS (ESRI ArcGIS). The results of potential photovoltaic technologies strongly depend on input data but not always roof data are accurate. The aim of this workis to define a tool to improve the results of a GIS simulation on urban scale. To validate the procedure, the results were compared with data monitored by PERSIL project. The analysis was based on the use of geographic information systems, data scanner laser (LiDAR), and software for 3D reconstruction of the buildings.